An Industry Level Analysis of Demand for Insurance in South Africa - Motsepe, Molatelo (Graduate School of Business (GSB), 2018)
The shaky political landscape in South Africa, resulting from high rate of corruption and political instability, is affecting economic growth. Among businesses, the use of insurance contracts has been advanced as one of the most effective risk management strategies to deal with the business risk. Insurance is designed to hedge against unforeseen and unplanned risks that may be attributable to manmade or natural disasters. One of the major reasons for purchasing insurance is to avert risk, whilst most firms in the manufacturing industry are driven by regulations to purchase insurance. The goal of this study was to analyse industry level demand for insurance as well as determine factors contributing to the demand for insurance by corporate firms in South Africa for the period between 2013 and 2014. This study used a multivariate approach to analyse data, to derive a clear picture of what transpires in the purchase of insurance and arrive at intelligent decisions. Multiple regression analysis was used to ascertain the factors contributing to the purchase of insurance as well as to identify dominant patterns in the data revealed by other empirical studies to understand the area under investigation. The study established six variables/factors that played an important role in the purchase of insurance. These were: firm size, operational leverage, industry type, underinvestment, turnover and depreciation and amortisation. The major players that positively influenced the demand for insurance were firm size and industry type followed by turnover, depreciation and amortisation respectively. It was also established that most firms in South Africa are regulated, therefore it was mandatory for firms to buy insurance to hedge against any risk. The policy and research implications of the findings are discussed.